The role of diet and nutrition in the etiology and prevention of oral diseases - Paula J. Moynihan (Bulletin of the World Health Organization, 2005)
Diet plays an important role in preventing oral diseases including dental caries, dental erosion, developmental defects, oral mucosal diseases and, to a lesser extent, periodontal disease. This paper is intended to provide an overview of the evidence for an association between diet, nutrition and oral diseases and to clarify areas of uncertainty. Undernutrition increases the severity of oral mucosal and periodontal diseases and is a contributing factor to life-threatening noma. Undernutrition is associated with developmental defects of the enamel which increase susceptibility to dental caries. Dental erosion is perceived to be increasing. Evidence suggests that soft drinks, a major source of acids in the diet in developed countries, are a significant causative factor. Convincing evidence from experimental, animal, human observational and human intervention studies shows that sugars are the main dietary factor associated with dental caries. Despite the indisputable role of fluoride in the prevention of caries, it has not eliminated dental caries and many communities are not exposed to optimal quantities of fluoride. Controlling the intake of sugars therefore remains important for caries prevention. Research has consistently shown that when the intake of free sugars is < 15 kg/person/year, the level of dental caries is low. Despite experimental and animal studies suggesting that some starch-containing foods and fruits are cariogenic, this is not supported by epidemiological data, which show that high intakes of starchy staple foods, fruits and vegetables are associated with low levels of dental caries. Following global recommendations that encourage a diet high in starchy staple foods, fruit and vegetables and low in free sugars and fat will protect both oral and general health.